1997
DOI: 10.2169/internalmedicine.36.479
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Aldose Reductase Inhibitors for Diabetic Gastroenteropathy with Constipation.

Abstract: Wepresent a diabetic patient with long-standing constipation complicated by paralytic ileus and septic shock. Shesuccessfully recovered from a critical condition, and her diabetes was well controlled. However,the constipation did not improve even after the administration of conventional medications. Epalrestat, an aldose reductase inhibitor (ARI), improved her bowel motility and autonomic cardiovascular dysfunction, as evident from her heart rate and blood pressure response. Gastroenteropathy is a major diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Jaspan et al 17) reported that ARI had an effect on both autonomic and somatic nerves. Nakamura at al 18) reported the effectiveness of ARI in the treatment of constipation in cases with diabetic gastroenteropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Jaspan et al 17) reported that ARI had an effect on both autonomic and somatic nerves. Nakamura at al 18) reported the effectiveness of ARI in the treatment of constipation in cases with diabetic gastroenteropathy.…”
Section: Discussionmentioning
confidence: 99%